Anticonvulsant, Anxiolytic, and Sedative Activities of Verbena officinalis - Khan, Abdul Waheed; Khan, Arif-ullah; Ahmed, Touqeer (Frontiers in Pharmacology, 2016)
We describe different neuropharmacological effects of Verbena officinalis crude extract (Vo.Cr). Pentylenetetrazole (PTZ)-induced seizures, elevated plus maze, light–dark box (LDB), open field and thiopental-induced sleeping test models were employed to evaluate Vo.Cr actions in mice. Vo.Cr dose-dependently (100–500 mg/Kg) delayed onset time of myoclonic jerks and tonic-clonic seizures, while decreased duration of tonic-clonic seizures (P < 0.05, P < 0.001 vs. saline group). Vo.Cr at 100 and 300–500 mg/Kg doses reduced animals’ mortality in PTZ-induced seizures test to 75 and 0%, respectively. Vo.Cr (50–300 mg/Kg) significantly increased time spent and number of entries into open arms, while decreased time spent and number of entries into closed arms (P < 0.05, P < 0.01, P < 0.001 vs. saline group), measured in elevated plus maze. Vo.Cr (50–300 mg/Kg) increased time spent in light compartment, while decreased time spent in dark compartment (P < 0.01, P < 0.001 vs. saline group) in LDB, like caused by diazepam. In open field test, Vo.Cr decreased number of ambulations and rearings frequencies, while increased the number of central squares crossings. In thiopental-induced sleeping test, Vo.Cr (50–300 mg/Kg) decreased onset time of sleep, while increased the duration of sleep (P < 0.05, P < 0.01, P < 0.001 vs. saline group). These results indicate that Verbena officinalis possess anticonvulsant, anxiolytic and sedative activities, which provides scientific background for its medicinal application in various neurological ailments, such as epilepsy, anxiety, and insomnia.